2013
DOI: 10.5194/bg-10-4481-2013
|View full text |Cite
|
Sign up to set email alerts
|

Tidal and seasonal carbon and nutrient dynamics of the Guadalquivir estuary and the Bay of Cádiz (SW Iberian Peninsula)

Abstract: To study the effects of the physical environment on carbon and nutrient cycle dynamics on the north-eastern shelf of the Gulf of Cádiz, changes in currents, tides, salinity, temperature, carbon system parameters (fugacity of CO2 (fCO2), dissolved organic carbon, dissolved inorganic carbon (DIC) and pH) and other related parameters(dissolved oxygen, total dissolved nitrogen (TDN), nutrients and suspended particulate matter) were measured in transects across the Guadalquivir estuary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The results strongly illustrate the need for higher temporal resolution data for the assessment of coastal carbon fluxes for this estuary, supporting previous similar claims by other researchers referring to other ecosystems [14,46,[56][57][58]. Therefore, the combination of seasonal point and transect evaluations with periodic diurnal measurements of system parameters will improve annual carbon budget calculations and may provide better numeric modelling of water quality.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results strongly illustrate the need for higher temporal resolution data for the assessment of coastal carbon fluxes for this estuary, supporting previous similar claims by other researchers referring to other ecosystems [14,46,[56][57][58]. Therefore, the combination of seasonal point and transect evaluations with periodic diurnal measurements of system parameters will improve annual carbon budget calculations and may provide better numeric modelling of water quality.…”
Section: Discussionsupporting
confidence: 86%
“…Studies on the inorganic carbon systems in coastal areas have reported high pCO 2 associated with upwelled waters, suggesting that upwelling is a source of both nutrient-rich and high CO 2 levels [45,46]. This occurrence, however, is not evident in the results, probably due to the strong influence of inner estuarine waters, frequently characterized by the same combination of nutrients and high pCO 2 .…”
Section: Seasonal Variabilitymentioning
confidence: 59%
“…Therefore, regional inputs of organic matter are likely to occur, which could well lead to an intensification in the ecosystem respiration and inorganic carbon accumulation with time. In addition, a considerable discharge of inorganic carbon from the Guadalquivir river estuary to the continental shelf of the GC has been measured 51,52 , which could be accounted as an extra DIC source for the NACW. These external inputs would contribute to the natural component affecting the decadal pH change in this water mass, which represented 40% of the total pH reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Turbulent mixing generated by tides and winds may mix acidic bottom water upward, leading to large changes in the airsea CO 2 flux (Cai et al, 2017;Paerl et al, 2018). Advection by tidal and wind driven currents across the horizontal gradient may cause large short-term pH fluctuations at fixed locations, which may add further stress to organisms for coping with extreme low pH events (Ribas-Ribas et al, 2013;Saderne et al, 2013;Pacellaa et al, 2018). There is an increasing recognition for the large temporal pH variability and extreme pH values in estuarine and coastal environments (Hofmann et al, 2011;Baumann et al, 2015;Baumann and Smith, 2018;Carstensen and Duarte, 2019), but most research has focused on metabolically driven pH fluctuations such as the diel photosynthesis/respiration cycle (Saderne et al, 2013;Baumann and Smith, 2018;Pacellaa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%